EKSPLOITASI SINERGI DIVERSIFIKASI - Sulastri, Sulastri (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
The motivation of a company to choose business diversification is amongst others are: (1) to gain synergy advantage from the use of shrafng assets that have the implication on joint cost and cost advantage. (2) to gain synergy advantage from risk sharing through developing product substitution for the purpose of risk overcoming from declining product cycle. (3) to gain synergy advantage from fund sharing which implcates fund transfer from one business unit to another. The exploitation of diversification of synergy done through many ways in the end are expected to produce performance. However, some studies found that companies that had diversified did not create value, specifically for companies that choose unrelated diversification strategies. This study focus on the determinants of the exploitation of the diversification of synergy: do companies diversify both related business or unrelated business to gain operational or financial synergy advantage which in the end will improve performance.The analysis done trouhg even study data (at the time diversification) from 1990 to 2002 with a sample at 110 companies. Data analysis techniques use structural equation model using AMOS Version 4. 1. In empirical test, samples are specified into 4 (four) groups which are : 1) full sample; samples are analyzed overall without distinguishing diversification strategic choice group and samples that are grouped based other characteristics diversification strategic choices that are : 1) dominant business, 2) related business, and 3) unrelated business. Based on the structural equation procedure in multivariate analysis, some assumption are tested: univariat outliers, multivariate outliers, normality and multicol/inierity. Then, the test results of the data based on multivariate analysis assumption of structural equation are presented.This study proves that diversification with financial synergy exploitation could be done through related or unrelated business. Financial synergy exploitation could use internal fund (free cash flow), external fund (debts) on the combination. However, the use of external fund reduces performance compared to the use of internal fund. The decreasing value occurs more on unrelated business compared to the related business. On the other hand operational synergy exploitation occures on related and dominant business but do not create value. The sources of non value creation on related business are caused by the inefficiency of internal transaction and over overinvestment. The sources of non value creation on dominant business are the inefficiency in the uses of assets and overinvestment.Â